2021
DOI: 10.1088/1742-6596/2070/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of potential probiotics isolated from fermented under-utilized Chrysophyllum albidum Linn kernels using microbiological, biochemical and molecular techniques

Abstract: Chrysophyllum albidum is a crop of commercial value in Nigeria, however, the seeds are either used for local games or thrown away. This study aimed at exploring this under-utilized kernel as a novel source for obtaining health beneficial bacteria with desired probiotic characteristics. Isolation of potential probiotic bacteria from naturally fermented C. albidum seeds was carried out and followed by their safety evaluation, Gram staining, catalase test, acid tolerance, bile tolerance, cellular hydrophobicity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Collection of the C. albidum seeds was done March 2020, and identification was done using the methods outlined by Odutayo et al 23 The C. albidum fruits for obtainment of the seeds were purchased at Afobaje market, Ota, Ogun State, Nigeria (popularly referred to as Oja Ota). The market is located at an approximate distance of 6.6841°N, 3.2153°E.…”
Section: Collection and Identification Of Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collection of the C. albidum seeds was done March 2020, and identification was done using the methods outlined by Odutayo et al 23 The C. albidum fruits for obtainment of the seeds were purchased at Afobaje market, Ota, Ogun State, Nigeria (popularly referred to as Oja Ota). The market is located at an approximate distance of 6.6841°N, 3.2153°E.…”
Section: Collection and Identification Of Seedsmentioning
confidence: 99%
“…(Nakai Japan, Patent no: 013219812). 23,24 Preparation of the Fermented and Unfermented Seeds Extracts This was done by applying the methods outlined by Odutayo et al 24 Both extracts were made by steeping the ground seeds in distilled water at 1:3 w/v, the mixtures were stirred, and stood for 24 hr at a temperature range of (25 to 28) o C. After 24 hr, filtration paper (Whatmann no. 1) was used for filtering each of the mixtures.…”
Section: Processing Of Seedsmentioning
confidence: 99%
“…The method described by Afolabi, Ahuekwe, Garuba, Adigun, Odutayo, and Adeyemi [3] was followed for the collection, culturing, and identification of the Enterococcus faecalis (MW481698) earlier authenticated as Gram-positive, catalase-negative, and non-hemolytic and deposited in the NCBI database [11]. The previously isolated bacteriocin-producing Enterococcus faecalis (MW481698) employed in the study was identified as non-hemolytic catalase-negative and Gram-positive bacteria [12]. A loopful of the isolate was suspended in 2 mL MRS broth before inoculation in a BHI broth and incubated at 200 rpm and 37 • C for 4-6 h in a shaker incubator.…”
Section: Handling Of Lactic Acid Bacteria For the Experimentationmentioning
confidence: 99%